2016
DOI: 10.1111/his.13010
|View full text |Cite
|
Sign up to set email alerts
|

HER2 gene copy number and breast cancer‐specific survival

Abstract: Increased copy number of HER2 may confer an increased risk of death from breast cancer despite negative HER2 status by ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…In addition, data on the prognostic impact of double-equivocal HER2 status remain controversial. 26 28 Our results on the relatively high frequency of TP53 mutations may support the contention that these cases constitute an aggressive subgroup of ER-positive carcinomas. This is in line with the risk-based stratification of the cohort provided by Prosigna analysis, which demonstrated high RORs, even within the subgroup of node-negative G2 carcinomas with tumor size <2 cm.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, data on the prognostic impact of double-equivocal HER2 status remain controversial. 26 28 Our results on the relatively high frequency of TP53 mutations may support the contention that these cases constitute an aggressive subgroup of ER-positive carcinomas. This is in line with the risk-based stratification of the cohort provided by Prosigna analysis, which demonstrated high RORs, even within the subgroup of node-negative G2 carcinomas with tumor size <2 cm.…”
Section: Discussionsupporting
confidence: 75%
“…HER2-positive breast cancer is a distinctive subtype that is associated with aggressive behavior and has a poorer outcome compared with HER2-negative disease [2]. Over the past 10 years, the addition of trastuzumab to chemotherapy has dramatically changed the clinical outcomes of patients with HER2-positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the HER2 gene is overexpressed in 15% of breast cancers, which is associated with increased tumor aggressiveness and thought to be associated with poor prognosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Both the HER2 /CEP17 ratio and the HER2 copy number were measured, and no significant effect on prognosis or benefit from trastuzumab was observed with different levels of HER2 amplification. In contrast, it was recently reported that there was an increased risk of death from BC in the first 5 years after diagnosis in women with HER2 copy numbers of ≥6, as well as of ≥4.0 and <6.0, irrespective of HER2 /CEP17 ratio . The conflicting clinical data suggest that the variability of the HER2 /CEP17 ratio and the HER2 copy number, depending on the number of cells counted, may determine the accuracy of the final result.…”
Section: Discussionmentioning
confidence: 99%